2020
DOI: 10.1037/apl0000426
|View full text |Cite
|
Sign up to set email alerts
|

An expanded conceptualization of line managers’ involvement in human resource management.

Abstract: Recent research provides evidence that, contrary to implicit assumptions in much of the strategic human resource management (SHRM) literature, human resource (HR) systems and practices are in fact enacted with substantial variation across units even within organizations, with such variation largely a function of the line managers involved in implementing HR practices in the units under their supervision. While instrumental in demonstrating the critical role that line managers play in facilitating the causal ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
119
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(133 citation statements)
references
References 112 publications
4
119
0
1
Order By: Relevance
“…We believe our paper also has important implications for two related literatures. First, our focus on leaders as orchestrators of the HCRE process connects well with and has implications for recent work exploring the impact of managers on the implementation of human resource management (HRM) practices (e.g., Kehoe & Han, 2020; Sikora, Ferris, & Van Iddekinge, 2015). Specifically, our emphasis on leadership's multilevel (individual, dyad, and group) and multifaceted (task and relational influences) impact on the emergence of human capital resources may provide additional theoretical perspectives to explore managers and their actions and behaviors when implementing HRM practices and engaging in workforce differentiation (Kehoe & Han, 2020).…”
Section: Implications For Related Literaturesmentioning
confidence: 86%
“…We believe our paper also has important implications for two related literatures. First, our focus on leaders as orchestrators of the HCRE process connects well with and has implications for recent work exploring the impact of managers on the implementation of human resource management (HRM) practices (e.g., Kehoe & Han, 2020; Sikora, Ferris, & Van Iddekinge, 2015). Specifically, our emphasis on leadership's multilevel (individual, dyad, and group) and multifaceted (task and relational influences) impact on the emergence of human capital resources may provide additional theoretical perspectives to explore managers and their actions and behaviors when implementing HRM practices and engaging in workforce differentiation (Kehoe & Han, 2020).…”
Section: Implications For Related Literaturesmentioning
confidence: 86%
“…In this vein, recent studies have considered line managers’ involvement in the HR implementation process to account for that variance ( Pak and Kim, 2018 ). However, most of them predominately focused on the antecedents and consequences of line managers’ HR implementation behavior ( Kehoe and Han, 2020 ); for instance, organizational culture ( Dewettinck and Vroonen, 2017 ), implementation-focused organizational climate ( Sikora and Ferris, 2014 ), and perceived HR support ( Dewettinck and Vroonen, 2017 ) have been positively linked to line managers’ HR implementation behaviors. Little attention has been paid to line managers’ leadership that may function as a medium through which these managers would better enable employees to understand HR practices in the direct influential process.…”
Section: Discussionmentioning
confidence: 99%
“…In this vein, Liao et al (2009), through empirical testing, found that there was a divergence between managers' perspective on HPWS and employee-perceived HPWS. However, the variance between implemented HPWS and employees' perceptions has been underexplained, and the pivotal role of line managers in predicting it has been overlooked (Nishii and Paluch, 2018;Kehoe and Han, 2020). Given that line managers often act as the intermediate linkage between intended HR function and employees and the proximal and direct resources for employees to gain information about HR practices, our primary purpose is to explore how line managers influence the alignment of HPWS.…”
Section: Introductionmentioning
confidence: 99%
“…2010; Van Mierlo et al . 2018), whereas others distinguish a set of beginning and end stages (Guest and Bos‐Nehles 2013); some see implementation as performed mainly by line managers (Kehoe and Han 2019; Sikora and Ferris 2014), whereas others include a wider variety of actors (Trullen et al . 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, such an approach does not take into consideration the possibility that HRM practices may change during implementation, as employees and line managers use them and try to integrate them into existing systems (Bos‐Nehles et al . 2017; Kehoe and Han 2019; Van Mierlo et al. 2018).…”
Section: Introductionmentioning
confidence: 99%